Seeing for Oneself: Agnes Deans Cameron’s Ironic Critique of American Literary Discourse in The New North - Johnstone, Tiffany (Nordlit, 2008)
In 1908, Agnes Deans Cameron, a schoolteacher, journalist and suffragist from Victoria, British Columbia, traveled from Chicago to the Arctic with her niece, Jessie Cameron Brown. Cameron followed the original 1789 route of Alexander Mackenzie and was intent on being one of the first white women to explore and document this northern territory (Roy, "Primacy" 56). She wrote about her trip in the popular book The New North, which was published in New York in 1909 by Appleton. While The New North is written by a Canadian author about Canada, it is deliberately aimed at an American audience. Not only was the book published in the United States, but the narrative also begins and ends in Chicago and repeatedly depicts her Canadian surroundings according to American frontier motifs.